Development and Validation of a Rodent Model of Amniotic Fluid Exchange: A Prospective Laboratory-Based Study - Braxton Forde; Samuel Martin; Jose L. Peiro (Clinical and Experimental Obstetrics & Gynecology)
Background: Significant interplay exists between the amniotic fluid and the developing fetus. However the true nature of the relationship between the amniotic fluid and the fetus, as well as the fetal membranes, is very poorly understood due to the lack of a feasible small animal model for amniotic fluid replacement, drainage, or oligohydramnios. We sought to create and present the feasibility of a rodent model of amniotic fluid exchange. Methods: Pregnant rats underwent midline laparotomy, trans-amniotic suture placement via either a U-stitch or a purse-string. Amniotic fluid was attempted to be drained via needle, and the remainder of the undrained fluid was allowed to drain passively, until the amniotic fluid was then replaced with either Normal Saline, Lactated Ringer’s, or a synthetic amniotic fluid. When oligohydramnios is desired, a catheter could be left transuterine to allow for continued fluid drainage. Results: We report the first successful model of complete amniotic fluid exchange in a rat model, successfully replacing the amniotic fluid with various synthetic fluids. A water-tight closure was achievable in all cases. This model is technically sound and reproducible, ensuring minimal fetal and maternal harm. Post procedure, there were no instances of preterm birth or rupture of membranes. In trials of this model, allowing for a brief period of surgical learning curve, we observed a less than 10% fetal loss rate following the procedure and a 0% preterm delivery rate. Conclusions: This novel model paves the way for more controlled examination of the intrauterine environment. It will allow researchers to examine the interplay between the components of the amniotic fluid and the developing fetus. It also opens potential for amniotic fluid exchange to be considered as a treatment option for various fetal conditions.